2020
DOI: 10.1016/j.mtbio.2020.100067
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell exosomes in bone regenerative strategies—a systematic review of preclinical studies

Abstract: The ability of bone for regeneration has long been recognized. However, once beyond a critical size, spontaneous regeneration of bone is limited. Several studies have focused on enhancing bone regeneration by applying mesenchymal stromal/stem cells (MSCs) in the treatment strategies. Despite the therapeutic efficacy of MSCs in bone regeneration, cell-based therapies are impeded by several challenges in maintaining the optimal cell potency and viability during expansion, storage, and final delivery to patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 76 publications
(539 reference statements)
2
70
0
1
Order By: Relevance
“…Each process is highly regulated and EVs are most probably involved in the cross-talk between the cells. This can be assumed from literature, demonstrating the positive impact of MSC EVs on fracture healing and bone regeneration ( Tan et al, 2020 ; Zhang et al, 2020 ). The study of Brady et al (2018) confirms our suggestion, it reported that shared as well as unique proteins were identified in serum-derived exosomes of dogs with a traumatic bone fracture in comparison to normal dogs.…”
Section: Discussionmentioning
confidence: 90%
“…Each process is highly regulated and EVs are most probably involved in the cross-talk between the cells. This can be assumed from literature, demonstrating the positive impact of MSC EVs on fracture healing and bone regeneration ( Tan et al, 2020 ; Zhang et al, 2020 ). The study of Brady et al (2018) confirms our suggestion, it reported that shared as well as unique proteins were identified in serum-derived exosomes of dogs with a traumatic bone fracture in comparison to normal dogs.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, extracellular vesicles (EVs), such as exosomes and microvesicles, have been attracting a strong research interest for use as natural drug delivery systems ( Chen et al, 2018 ; Tang and Wang, 2020 ). Mesenchymal stem cell (MSC)-derived exosomes have been reported to be involved in multiple physiology and pathology activities including osteogenesis, bone regeneration, osteoarthritis, cardiomyoblast hypoxia–reperfusion, cognitive impairment, inflammation, stroke, sepsis, and tumorigenesis ( Zheng et al, 2018 ; Huang et al, 2020 ; Jin et al, 2020 ; Nakano et al, 2020 ; Tan et al, 2020 ; Venkat et al, 2020 ; Xu et al, 2020 ; Zou et al, 2020 ). Jia et al (2020) report that exosomes secreted by young MSCs promote osteogenesis and bone formation in older rats.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown the therapeutic potential of exosomes in treating various bone diseases [30,31]. The bone mineral density of bovine colostrum exosome-fed glucocorticoid-induced osteoporosis mice was signi cantly improved compared with that of control mice without exosome treatment [32].…”
Section: Discussionmentioning
confidence: 99%